The largest thalattosuchian (Crocodylomorpha) supports teleosaurid survival across the Jurassic-Cretaceous boundary. (June 2016) - Fanti, Federico; Miyashita, Tetsuto; Cantelli, Luigi; Mnasri, Fawsi; Dridi, Jihed; Contessi, Michela; Cau, Andrea
Abstract: A new teleosaurid from the Lower Cretaceous of Tataouine (Tunisia), Machimosaurus rex sp. nov., definitively falsifies that these crocodylomorphs faced extinction at the end of the Jurassic. Phylogenetic analysis supports its placement closer to M. hugii and M. mosae than M. buffetauti . With the skull length up to 160 cm and an estimated body length of 10 m, M. rex results the largest known thalattosuchian, and the largest known crocodylomorph at its time. This giant thallatosuchian probably was an ambush predator in the lagoonal environments that characterized the Tethyan margin of Africa during the earliest Cretaceous. Whether the Jurassic-Cretaceous mass extinction was real or artefact is debated. The discovery of M . rex supports that the end-Jurassic crisis affected primarily Laurasian biota and its purported magnitude is most likely biased by the incomplete Gondwanan fossil record. The faunal turnovers during the J-K transition are likely interpreted as local extinction events, triggered by regional ecological factors, and survival of widely-distributed and eurytypic forms by means of habitat tracking. Graphical abstract: Highlights: Machimosaurus rex is a new teleosaurid crocodylomorph from Tunisia. It is the largest known thalattosuchian, up to 10 m in length. M. rex, the first Cretaceous teleosauroid found, was the last-surviving of its group.